Geographical and sectorial distribution of infrastructure projects by private participation in the world and sub-Saharan Africa for the period 1990-2017 - Saleh, Qusay Mahjoub Mohammed; Al Mahal, Abdul Azim Suleiman (Journal of Economic, Administrative and Legal Sciences, 2019)
The paper examines geographical distribution and sectorial distribution in the world and sub-Saharan Africa for infrastructure projects, which are held with the participation of the private sector. The problem of the study is the growing demand for development services, especially infrastructure services and facilities, to meet the requirements of economic development and the shortage of resources for the public sector. aims to show the strength and success of the experience of infrastructure projects with the participation of the private sector in the world and the countries of sub-Saharan Africa, and monitoring and clarifying the geographical and sectorial distribution to explain which group of countries and which sectors received a larger share, The paper’s hypothesis is that there has been a marked increase in investment in infrastructure with the participation of the private sector in the period 1990-2017. Private sector investments are concentrated in the fast-yielding sectors and the ease and clarity of ways of retrieving returns in the period under study. The most important results, reaching active projects of the total infrastructure projects with the participation of the private sector to 94% and not exceeding 5% of the world’s 98% of the world’s sub-Saharan countries, indicates the success of their experience and effectiveness of the construction and operation, The private sector’s tendency to invest in infrastructure by focusing on sectors that are more privatized than others, such as the energy, electricity and telecommunications sectors, are characterized by their high profitability and low risk related with their construction, operation, ease and clarity of cost recovery, The paper recommended the necessity to invest by focus of the on facilities and guarantees to enter the private sector in the sectors of communications and energy with high potential for investment Also try to solve the obstacles facing private sector access to partnership in other infrastructure sectors by providing more guarantees and customs and tax exemptions, create an appropriate environment by strengthening the investment base of partnership projects by providing legal structures, rules and procedures and unifying them, provide economic stability in the rate of inflation and exchange rate and interest and political stability and security for the growth of partnership and strengthen and attract the private sector to them, strengthen the inter-private relations between the sub-Saharan African countries to enhance the efficiency, participation and integration of the private sector in joint infrastructure projects that transcend one country in a similar geographical and economic environment and development objectives.